2009
DOI: 10.1111/igc.0b013e3181a8ba85
|View full text |Cite
|
Sign up to set email alerts
|

Is Complete Surgical Staging Necessary in Clinically Early-Stage Endometrial Carcinoma?

Abstract: The purpose of this study was to evaluate the incidence of pelvic/para-aortic node metastases and the other pathological characteristics from medical records of patients with endometrial carcinoma treated at King Chulalongkorn Memorial Hospital, Bangkok, Thailand, between 1996 and 2005. The records of 213 patients with endometrial carcinoma who had complete surgical staging were reviewed. A particular focus was on clinically early-stage disease. Clinical staging could be determined in 206 patients. Of the 206 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Myometrial invasion and histological grade are the most important prognostic indicators in endometrial cancer, with a good correlation with the prevalence of lymph node metastases and with patient survival. Tumor grade is the most commonly used prognostic factor that guides surgical planning [6]. In the PORTEC randomized trial, stage I patients (excluding stage I C grade 3 patients) operated without performing lymphadenectomy were randomized to receive pelvic radiotherapy or no treatment, with no diVerence in global survival and in endometrial cancer-related death, with a justiWed morbidity [7].…”
Section: Discussionmentioning
confidence: 99%
“…Myometrial invasion and histological grade are the most important prognostic indicators in endometrial cancer, with a good correlation with the prevalence of lymph node metastases and with patient survival. Tumor grade is the most commonly used prognostic factor that guides surgical planning [6]. In the PORTEC randomized trial, stage I patients (excluding stage I C grade 3 patients) operated without performing lymphadenectomy were randomized to receive pelvic radiotherapy or no treatment, with no diVerence in global survival and in endometrial cancer-related death, with a justiWed morbidity [7].…”
Section: Discussionmentioning
confidence: 99%
“…9,10 In a previous report, the rate of lymphedema complication in a group of patients who underwent pelvic and para-aortic lymphadenectomy for gynecologic malignancies was found to be 24%. 11 The same researchers suggested that if the surgical approach could be modified, the severity of lymphedema might be reduced.…”
Section: Discussionmentioning
confidence: 97%
“…[ 21 ] Previous studies have emphasized that the detection of occult lymph node metastasis was important for predicting prognosis, showing that 4.1% to 5.6% of the patients with low-risk endometrial cancer may have lymph node metastasis on the final histologic reports. [ 22 , 23 ] In patients with intermediate- or high-risk endometrial cancer, lymph node metastasis was observed in 21.9% of the patients, of which, para-aortic lymph node involvement rate up to 15%. [ 21 ] Moreover, a growing number of studies found that the skip metastasis, namely isolated para-aortic lymph node metastasis in the setting of negative pelvic nodes, has been reported in less than 5% of patients but mostly associated with risk factors for lymph node involvement.…”
Section: Discussionmentioning
confidence: 99%